Imran Nazar Hosein's Interpretation of the End Times: Rudolf Bultmann's Hermeneutical Analysis of Demythology - Ulviana, Ulviana; Faiz, Fahruddin; Carvalho, Adriano da Silva (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
whether his interpretations are grounded in a coherent epistemological framework or primarily driven by intuitive reflection. The analysis draws on Rudolf Bultmann's hermeneutic theory of demythology as a comparative lens, given its focus on reinterpreting mythological elements to address existential concerns, particularly in the context of discussions about the future rather than historical facts. The research employs a literature-based approach, utilizing primary sources such as Hosein's works on eschatology and Bultmann's writings on demythology, alongside secondary sources from relevant academic literature. The findings reveal notable methodological parallels between Hosein’s interpretations and Bultmann’s demythologization, particularly in their shared use of hermeneutic techniques. However, a key distinction lies in their epistemological foundations: while Bultmann approaches the New Testament through a Christian existentialist lens, Hosein’s interpretations are deeply rooted in Sufi epistemology and his perspective as a Muslim scholar interpreting the Qur'an.